Methods for the study of marine benthos - Eleftheriou, Anastasios, 1935- (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
"Originally put together by the International Biological Programme (IBP) and published in its first edition in 1971, this book was well received and subsequently published a second edition in 1984. After a gap of nearly 20 years the third edition was published by Blackwell Publishing in 2005. That third edition has become a well used and respected book and has so far sold 982 copies (current price of the third edition is £104.99 / US$204.99)"--
"Completely revised and updated fourth edition of this essential tool book, containing much new information of great importance to marine scientists, oceanographers, environmental scientists and ecologists"--
Design and analysis in benthic surveys in environmental sampling / Anthony J Underwood, Maura G Chapman -- Characterising the physical properties of seabed habitats / Andrew J Kenny, Ian Sotheran -- Imaging techniques / Chris J Smith, Heye Rumohr -- Diving / Colin Munro -- Macrofauna techniques / Anastasios Eleftheriou, Derek C Moore -- Meiofauna techniques / Paul J Somerfield, Richard M Warwick -- Deep-sea benthic sampling / Alan J Jamieson, Ben Boorman, Daniel OB Jones -- Measuring the flow of energy and matter in marine benthic animal populations / Jan van der Meer, Thomas Brey, Carlo Heip, Peter MJ Herman, Tom Moens, Dick van Oevelen -- Phytobenthos techniques / Hans Kautsky -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Dredging (Biology); Benthos -- Research -- Methodology; Marine biology -- Methodology; TECHNOLOGY & ENGINEERING -- Fisheries & Aquaculture; NATURE -- Animals -- Marine Life; Benthos -- Research -- Methodology; Dredging (Biology); Marine biology -- Methodology; Benthonische fauna; Benthonische flora; Mariene ecologie; Wetenschappelijke technieken; Electronic books